Analisis Semiotika Komunikasi Pesan Moral Tentang Kekerasan Seksual Dalam Film Penyalin Cahaya - Andini, Puri; Kusumo, Yudhy Widya (Jurnal Paradigma, 2023)
The Komnas Perempuan commissioner stated that there were 2,363 cases of sexual violence in 2021, and from January to July in 2022 there were 1,241 cases of sexual violence. This phenomenon can occur by both men and women, where the position of the victim does not receive empathy instead of protection from the authorities. Film which is a form of mass media is often used by filmmakers to describe the reality that occurs in society. Semiotic analysis of film aims to interpret phenomena as signals or as meaningful things through the study of the code signs made by filmmakers. The analysis of semiotics in this study is reviewed through the theory by Ferdinand de Saussure which defines semiotics as a science that examines the role of signs as part of social life. By distinguishing the signifier and signified contained in the film with reference to the conveyance of the intended meaning of the sign. The method used is a qualitative research method with data collection through content analysis and interviews. The film that is the object of research is the Film Copying Light by Wregas Bhanuteja. The results of the semiotic analysis of the communication of moral messages about sexual violence in the film Copying Light are the existence of powerrelations between victims and perpetrators,genderbased violence, the struggle of victims in seeking justice, the lack of a legal framework that is enforced, the helplessness of victims because they are silenced by the system, as well as several signs and signs in every scene or scene it turns outto have a meaning that is closely related to the phenomenon of sexual violence.